Analisis Keefektifan Kalimat pada Teks Berita Artikel CNN Indonesia Mengenai Pemilu Edisi Februari 2024 sebagai Kelayakan Bahan Ajar Membaca Kritis Siswa Kelas IX SMP - Adhela Fathma Setiyani; Adhitya Indra Pratama Putra; Choirunnisa Aprilia; Nayla Putri Dewi Lestari; Sekar Cahya Ningrum; Asep Purwo Yudi Utomo; Ruly Indra Darmawan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
A news text is a text that conveys news or information to the public about a factual and actual event. In the writing of news text should pay attention to the effectiveness of sentences so that the information conveyed can be accepted by readers and listeners. So, this research focuses more on analyzing the effectiveness of sentences contained in news text excerpts. The purpose of this study is to describe the effectiveness of sentences in news texts for critical reading of grade IX junior high school students. This type of research is qualitative research with descriptive method while the research data collection uses literature study techniques, namely listening and noting. The results of this study prove that sentence analysis shows the existence of effective sentences and ineffective sentences. Sentences are classified as effective if they meet several requirements, namely structural equivalence, word economy, accuracy of reasoning and logicality of language. Meanwhile, ineffective sentences are caused by the structure of the sentence not being unified, not parallel, and very wasteful or wordy. The practical benefit obtained is the ease of determining the effectiveness of sentences in news texts. The data taken in this research is in the form of effective sentences contained in CNN news articles about the February edition of the election for critical reading of grade IX junior high school students.